Kroonisen mangaanisulfaattialtistuksen (MnSO4) vaikutus seeprakalojen lisääntymiseen ja pituuskasvuun - Wynne-Ellis, Miika (2023)
Many metals, such as manganese, are essential for fish. As their concentration in aquatic environment increase, they can cause several reproductive and growth challenges among exposed individuals. The effects are different for different sizes of fish and in different populations and, particularly as fishing pressure affects the size of individuals, it is important to study how different levels of exposure affect different sizes of individuals. In this observational study, the reproduction and length growth of zebrafish (Danio rerio) of small and large selection lines exposed to manganese sulphate (MnSO4) were investigated at different levels of manganese sulphate exposure (control, 0,017, 0,05, 1,5, 3,5 and 7,5 mg/l). The number of eggs and the proportions of dead, unfertilized, and live eggs and egg survival were observed. For length growth, the length of fish was observed weekly from 77 days to 161 days. The length growth of individuals was also compared with that of the mother fish, to detect a transgenerational effect. Statistically significant differences in exposure were observed between the sampling lines in terms of number of eggs, number of deaths and survival. For growth, no statistically significant difference was found between the selection lines for different exposures. However, exposure affected the growth of both selection lines equally. Manganese sulphate exposure may affect the reproduction of individuals of different sizes based on this study.